THE CRIME OF RAPE: AN ANALYSIS FROM THE FEMINIST LEGAL THEORY PERSPECTIVE - Maychellina; Sabina, Vina; Prameswari, Fareh (LPPM, Universitas Muhammadiyah Riau, 2023)
Rape is a crime that seriously impacts victims and society, especially women. In this research, feminist legal theory is used as a basis for analyzing the regulation of the crime of rape. feminist legal theory emphasizes placing women as the main actors in decision-making and upholding women's rights in any form. feminist legal theory emphasizes establishing women as the main actors in decision-making and defending women's rights in any form. This theory sees violence against women as a form of gender discrimination, where the parties who are most often victims are women. In feminist legal theory, violence against women occurs because of gender inequality and the power held by men in the legal system. The author analyzes the criminal act of rape regulated in positive law in Indonesia in protecting women. This research aims to find out how the crime of rape is regulated and how criminal acts are regulated from the perspective of Feminism Legal Theory. This writing uses a normative juridical method with a statutory and conceptual approach. This research shows that referring to feminist legal theory, the sexual violence crime law is a positive step in eliminating gender-based violence and providing justice for rape victims.